Motivasi Mahasiswa dalam Mendaki Gunung Gamalama Sebagai Wisata Minat Khusus: (Studi Kasus Mahasiswa di Universitas Khairun, Universitas Muhammadiyah dan Stikip) - Fitria Soamole; Muslim Fadel (TOBA: Journal of Tourism, Hospitality, and Destination, 2023)
Against the backdrop of increasing competition in life, everyone is busy with routine, resulting in tension, boredom and boredom, so they use their free time as time to restore mental health to gain fresh thinking and calm. One form of leisure activity carried out is traveling. The tourist activities currently carried out vary greatly, each person who goes on a tourist trip has different motivations. There are several factors that motivate travel, including entertainment, education, health and business. Tourism activities are closely related to visitor motivation. The motivation for traveling is traveling to obtain a temporary life in the natural environment. The aim is to determine the motivation of tourists to climb Mount Gamalama. Quantitative method to obtain data on the motivation of tourists to climb Mount Gamalama. While qualitative is for analyzing. Findings from 72 respondents: 24 tourists chose number 5, which is very important because the attraction of Mount Gamalama is one of the main factors that attracts tourists and 29 respondents chose number 4 on the grounds of pristine natural beauty, beautiful natural scenery, being able to see the sunrise, the expanse of the islands. The island can be seen from a height and the main factor is Mount Merapi which is still active today